Core Competency Development Pathways for Navigation Technology Students Oriented to the Staged Evolution of Autonomous Navigation in Intelligent Ships - Liu, Xiao; Wu, Yong; Wang, Cong; Deng, Hua (Journal of Educational Theory and Practice, 2026)
The development of autonomous navigation in intelligent ships is reshaping the competency structure and occupational orientation of students majoring in Navigation Technology. Drawing on the IMO MASS Code and the China Classification Society Rules for Intelligent Ships (2026), this study examines five typical stages: automated assistance and decision support, remote control with crew on board, remote control without crew on board, autonomous operation with human-machine collaboration, and full-voyage autonomy with shore-based supervision. On this basis, a core competency development framework is proposed, consisting of stage evolution, job transformation, competency needs, and educational pathways. The study argues that, in addition to conventional seamanship, students should develop competencies in smart navigation equipment, remote control, autonomous navigation system supervision, human-machine collaboration, data analysis, shore-based operations management, and regulatory safety. Accordingly, pathways are proposed for reconstructing training objectives, optimizing the curriculum, reforming practical teaching, developing integrated teaching platforms, and improving competency-oriented assessment. The findings provide a reference for educational reform in Navigation Technology programs under the development of intelligent ships.